Transformational leadership and employee voice behavior - Luthfyrakhman, Haveel (2017)
This study intends to determine the relationship between transformational leadership and employee voice behavior among workers in XYZ Resort, Bintan, Indonesia. There are six dimensions of transformational leadership: articulating a vision, providing an appropriate model, fostering the acceptance of group goals, high performance expectations, individualized support and intellectual stimulation (Podsakoff, et al., 1990). A set of questionnaire consisted of instruments by Podsakoff, et al., (1990) in measuring transformational leadership and Van Dyne and LePine (1998) in measuring employee voice behavior were used. A total of 169 questionnaires were distributed using simple random sampling method and collected. Descriptive analysis results showed that in XYZ Resort, the level of transformational leadership and the level of employee voice behavior was high. The result also showed that transformational leadership was significantly correlated with employee voice behavior. And as expected, the result also showed that each of six dimensions of transformational leadership were significantly correlated with employee voice behavior.